Análise dos impactos da entrada em operação da companhia siderúrgica do Pecém no Ceará utilizando o modelo insumo-produto - Lima, Igor do Carmo (2019)
This paper analyzes the estimated impacts on variables such as production, employment and income in the state of Ceará and the rest of Brazil, with the start of operations of a large industry, in this case, Companhia Siderúrgica do Pecém (CSP) located in city of São Gonçalo do Amarante. These impacts were estimated using the Interregional Input-Output Model, with the economy divided into 24 sectors and regionalized in Ceará and Rest of Brazil, to capture direct and indirect impacts. The results indicate that the impacts stand out in Ceará in relation to the rest of Brazil, which can be observed in the impact on the Gross Domestic Product (GDP) of Ceará and Brazil, given respectively by 3.69% and 0.11%, and labor force of Ceará and Brazil, given respectively by 1.67% and 0.08%. This study considers the economic structure of 2008, which is the reference year of the matrix used.